The Informal Organization of the Soviet Firm - Berliner, Joseph S. (Quarterly Journal of Economics, 1952)
I. Introduction, 342. — II. Sources and reliability, 343. — III. Goals of managerial behavior: premia, profits, the quiet life, 347. — IV. Informal behavior principles of management: the safety factor, simulation, blat, 353. — V. Expectations facilitating informal methods, 358. — VI. Characteristics of the economic system, 361. — VII. Conclusion, 364.